Lesson observation tool for project-based learning: a useful tool for learner-centered pedagogy enhancement - Ukobizaba, Fidele; Maniraho, Jean Francois; Uworwabayeho, Alphonse (Frontiers in Education, 2025)
IntroductionThe CBC has been implemented in pre-primary through secondary schools in Rwanda. However, a gap was found in assessing the implementation of the CBC since there is no documentation to fulfill the need.MethodologyThis study is a product of a validated and reliable Lesson Observation Tool for Project-based Learning (LOTPBL), designed to fill the gap in monitoring and assessing the implementation of a competence-based curriculum within a project-based learning (PjBL) framework in Rwanda. The tool was piloted to check for its construct. The tool was checked for reliability. The calculated Kappa coefficient was 0.8, indicating that the tool is suitable for use. The tool was used while observing one teacher during 60 lessons (30 lessons before and 30 after the intervention).ResultsThe tool was found worthy to be used during lesson observations about project-based learning instructions. The analysis of the collected sample data revealed an improvement in the teacher employing key observations of PjBL during instructions (p-value = 0.0096; p < 0.05). The computed t-statistic of −3.38 with a two-tailed p-value of 0.0096 (p < 0.05) confirms that this improvement is statistically significant.DiscussionThese results indicate a notable enhancement in the implementation of strategies such as project initiation, student-centered learning, collaboration, and authentic assessment during instructions. The LOTPBL holds significant potential for supporting the global shift toward competency-based and active learning methodologies through project-based learning.